Strategic Planning Process in a General Rural Hospital: An Experience at Dr. Ambrosoli Memorial Hospital, Uganda - Carlo Lonati, Andrea; Polloni, Ilaria; Ciantia, Filippo; Odong, Thomas; Pontello, Mirella (JUNCO – Journal of Universities and international development Cooperation, 2018)
Dr. Ambrosoli Memorial Hospital is a general rural hospital located in Kalongo (Northern Uganda). The hospital is facing new difficulties that call for urgent actions, which imposed a plan for its de-velopment. The strategic planning process was guided by engagement of stakeholders through a step-by-step participatory process. The plan acknowledges four Strategic Goals that integrate different dimensions (economic, social and environmental) around the themes of service delivery, infrastructure, partnership and education. The purpose is to communicate the hospital’s strategic vision, creating a framework that enables to prepare work plans and budgets, as well as monitor progresses over time.
Keywords: Rural hospital; Strategic plan; Participatory design